Answer:
x - intercept: (-22, 0)
y - intercept: (0, 11)
Explanation:
Given the linear equation
-3x + 11y = 66
Determining the x-intercept
We know that the x-intercept can be computed by setting the value y=0 and solving for x.
substitute y = 0
-3x + 11y = 66
-3x + 11(0) = 66
-3x + 0 = 66
-3x = 66
Divide both sides by -3
-3x/-3 = 66/-3
x = -22
Thus, the ordered pair representing the x-intercept : (-22, 0)
Determining the y-intercept
We know that the y-intercept can be computed by setting the value x=0 and solving for y.
substitute x = 0
-3x + 11y = 66
-3(0) + 11y = 66
0 + 11y = 66
11y = 66
Divide both sides by 11
11y/11 = 66/6
y = 11
Thus, the ordered pair representing the y-intercept : (0, 11)
Therefore, we conclude that:
x - intercept: (-22, 0)
y - intercept: (0, 11)